Sequencing of neurofilament genes identified NEFH Ser787Arg as a novel risk variant of sporadic amyotrophic lateral sclerosis in Chinese subjects - Feng Lin; Wanhui Lin; Chaofeng Zhu; Jilan Lin; Junge Zhu; Xu-Ying Li; Zhanjun Wang; Chaodong Wang; Huapin Huang (BMC, 2021)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease with neuronal cell inclusions composed of neurofilaments and other abnormal aggregative proteins as pathological hallmarks. Approximately 90% of patients have sporadic cases (sALS), and at least 4 genes, i.e. C9orf72, SOD1, FUS and TARDBP, have been identified as the main causative genes, while many others have been proposed as potential risk genes. However, these mutations could explain only ~ 10% of sALS cases. The neurofilament polypeptides encoded by NEFH, NEFM, and NEFL are promising protein biomarkers for ALS and other degenerative diseases. However, whether the genetic variants of these genes were associated with ALS remain ambiguous. Methods Here, we used PCR-Sanger to sequence the exons of these three genes in a cohort of 371 sALS patients and 711 healthy controls (Phase I) and validated the risk variant in another 300 sALS patients and 1076 controls (Phase II). Results A total of 92 variants were identified, including 36 rare heterozygous variants in NEFH, 27 in NEFM, and 16 in NEFL, and only rs568759161 (p.Ser787Arg) in NEFH reached nominal statistical power (P = 0.02 at Phase I, P = 0.009 at Phase II) in the case-control comparison. Together, the Phase I and II studies showed the significantly higher frequency of the variant in cases (9/1342, 0.67%) than in controls (2/3574, 0.07%) (OR 12.06; 95% CI 2.60-55.88; P = 0.0003). No variants passed multiple testing in the discovery cohort, but rs568759161 was associated with ALS in a replication cohort. Conclusions Our results confirmed that NEFH Ser787Arg is a novel sALS risk variant in Chinese subjects, but NEFM and NEFL were not associated with sALS. These data may have implications for genetic counselling and for understanding the pathogenesis of sALS.